2017
DOI: 10.1007/s11606-017-4217-5
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Expansion, Mental Health, and Access to Care among Childless Adults with and without Chronic Conditions

Abstract: Medicaid expansion was associated with substantial improvements in mental health and access to care among low-income adults with chronic conditions. These positive trends are likely to be reversed if Medicaid expansion is repealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 27 publications
(43 reference statements)
4
69
2
Order By: Relevance
“…Estimates of changes in out‐of‐pocket costs ($215 vs $237) and any prescription medication use (11.6 percentage points vs 12.1 percentage points) were very similar to those found in a randomized control trial after 2 years of Medicaid enrollment . Finally, even after adjustment, Medicaid enrollment was associated with statistically significant reductions in severe psychological distress, a finding that is similar to previous evaluations that found Medicaid expansion under the ACA was associated with significant reductions in psychological distress, poor mental health days, and depression …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Estimates of changes in out‐of‐pocket costs ($215 vs $237) and any prescription medication use (11.6 percentage points vs 12.1 percentage points) were very similar to those found in a randomized control trial after 2 years of Medicaid enrollment . Finally, even after adjustment, Medicaid enrollment was associated with statistically significant reductions in severe psychological distress, a finding that is similar to previous evaluations that found Medicaid expansion under the ACA was associated with significant reductions in psychological distress, poor mental health days, and depression …”
Section: Discussionsupporting
confidence: 81%
“…evidence stemming from these experiments suggests Medicaid has positive effects on access to care, health, and financial security. [8][9][10][11][12][13][14] For example, Medicaid expansion under the ACA led to an 8.2 percentage point improvement in insurance coverage, 5 a 12.1 percentage point increase in access to primary care, 15 a 3.4 percentage point decrease in self-reported lifetime depression diagnoses among individuals with chronic conditions, 8 and a decrease in unpaid medical bills of $3.4 billion over 2 years. 10 Although the population-level effects of state Medicaid expansions (i.e, average treatment effects) are well documented, less is known about Medicaid's direct impact among people who gain Medicaid after a period of uninsurance (i.e, average treatment effect on the treated).…”
mentioning
confidence: 99%
“…The characteristics of the sample of adults with chronic conditions differed by whether or not they resided in an expansion state. Compared with individuals in nonexpansion states, individuals in expansion states were younger (< 35 years), more likely to be Hispanic, unmarried, have a high school education, and have higher rates of unemployment …”
Section: Impact Of the Ppacamentioning
confidence: 99%
“…Using data from the 2011–2015 BRFSS, Winkelman et al. reported a significant improvement in self‐reported health among adults with chronic conditions with reduction in poor mental—but not poor physical—health . Individuals without chronic conditions did not report significant health improvement.…”
Section: Impact Of the Ppacamentioning
confidence: 99%
“…1 The authors use a large national survey to compare self-reported access to care and days of poor health in the last month before and after the Medicaid expansion among individuals residing in expansion versus non-expansion states, and stratifying by whether individuals reported ever being diagnosed with a chronic condition. The authors find that individuals with at least one chronic condition residing in expansion states experienced reductions in total days in poor health, and that the improvements were mainly driven by fewer reported days of poor mental health.…”
mentioning
confidence: 99%